De novo genome assembly and population genomics of a shrub tree Barthea barthei (Hance) krass provide insights into the adaptive color variations - Huang, Weicheng; Xu, Bin; Guo, Wei; Huang, Zecheng; Li, Yongquan; Wu, Wei (Frontiers in Plant Science, 2024)
Flower color is a classic example of an ecologically important trait under selection in plants. Understanding the genetic mechanisms underlying shifts in flower color can provide key insights into ecological speciation. In this study, we investigated the genetic basis of flower color divergence in Barthea barthei, a shrub tree species exhibiting natural variation in flower color. We assembled a high-quality genome assembly for B. barthei with a contig N50 of 2.39 Mb and a scaffold N50 of 16.21 Mb. The assembly was annotated with 46,430 protein-coding genes and 1,560 noncoding RNAs. Genome synteny analysis revealed two recent tetraploidization events in B. barthei, estimated to have occurred at approximately 17 and 63 million years ago. These tetraploidization events resulted in massive duplicated gene content, with over 70% of genes retained in collinear blocks. Gene family members of the core regulators of the MBW complex were significantly expanded in B. barthei compared to Arabidopsis, suggesting that these duplications may have provided raw genetic material for the evolution of novel regulatory interactions and the diversification of anthocyanin pigmentation. Transcriptome profiling of B. barthei flowers revealed differential expression of 9 transcription factors related to anthocyanin biosynthesis between the two ecotypes. Six of these differentially expressed transcription factors were identified as high-confidence candidates for adaptive evolution based on positive selection signals. Transcriptome profiling of B. barthei flowers revealed differential expression of 9 transcription factors related to anthocyanin biosynthesis between the two ecotypes. This study provides insights into the genetic basis of flower color divergence and the evolutionary mechanisms underlying ecological adaptation in plants.